TRANSFORMATIONS IN THE SOCIOLOGICAL PERCEPTIONS OF CHILDHOOD - Karapetyan, Tatevik (Journal of Sociology: Bulletin of Yerevan University, 2025)
The article explores the evolution of the position, role, and status of childhood and children as a social category through the lens of sociological thought. In particular, it examines the religious, economic, political, and social influences that have shaped the historical dynamics of childhood perceptions. The article also analyzes the process by which sociology has come to recognize childhood, especially in the context of the concepts "sociological child" and "pre-sociological child” and discusses the current discourse on the interpretation of childhood from constructivist perspectives. Further, the article reflects on how these evolving perceptions influence decision-making concerning children, the development of child protection policies, and the nature of research conducted on children. The analysis synthesizes the multilayered and polysemous nature of childhood as a shifting social status that is shaped by historical, political, and social contexts. This understanding highlights the need to reframe the “position” of the child as a subject in the broader context of the transition from a vulnerability-based approach to one grounded in children’s rights.